IMPLEMENTASI KEBIJAKAN PERLINDUNGAN KHUSUS ANAK PADA DINAS PENGENDALIAN PENDUDUK, KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN GUNUNG MAS - Hernitawati, Hernitawati; Pasaribu, Muhammad Irvan Yazid Azhar (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to analyze the implementation of special child protection policies at the Population Control, Family Planning, Women's Empowerment, and Child Protection Office of Gunung Mas Regency. The underlying issues are the continued presence of children who are victims of violence and the suboptimal coordination between agencies in handling child protection cases. This study uses a qualitative descriptive approach based on George C. Edward III's policy implementation theory, which encompasses four aspects: communication, resources, implementer disposition, and bureaucratic structure. Data were obtained through in-depth interviews, observations, and documentation of parties involved in policy implementation. The results indicate that the implementation of special child protection policies in Gunung Mas Regency has been quite successful in terms of communication and implementer disposition, but still faces challenges due to limited human resources and cross-agency coordination. Therefore, increasing the capacity of the apparatus, strengthening synergy between agencies, and providing adequate budget support are needed to ensure optimal and sustainable implementation of child protection policies in Gunung Mas Regency. This research is expected to provide input for local governments in strengthening the implementation of child protection policies at the local level.